Effect of Berenuk Fruit Extract (Crescentia cujete L.) on Mortality of Plutella xylostella on Mustard Plants - Feri Bakhtiar Rinaldi; Taupik Sopyan; Jeti Rachmawati; Ai Nurfadilah (Quagga: Jurnal Pendidikan dan Biologi, 2025)
Mustard production in Indonesia in 2022 decreased by 2.9% from the previous year, caused by the Plutella xylostella attack. Efforts to control P. xylostella usually uses synthetic pesticides but harms the environment, so other alternatives are needed. Vegetable pesticides derived from Berenuk fruit (Crescentia cujete) containing phenol compounds, alkaloids, flavonoids, tannins, steroids, and saponins have the potential to control the population of P. xylostella. This study aimed to determine the effect of berenuk (C. cujete) extract on P. xylostella mortality. This study used an experimental method with a research design in the form of a Randomized Group Design consisting of 6 treatments and 4 replicates, namely the provision of test extracts with concentrations of 0%, 6.25%, 12.5%, 25%, 50%, and 100%. Observations of mortality of test larvae were made at 24, 48, and 72 hours after the test. Based on Probit analysis for LC10, LC25 and LC50 showed that for LC10 = 1.377%, LC25 11.549% and LC50 the lowest was 55.9%. Berenuk fruit extract (C. cujete) affects the mortality of P. xylostella; the higher the concentration of the extract, the higher the ability to control the population of Plutella xylostella.